How to survive? An analysis on the development of China's stock markets - Yang, Ameng (2006)
With advent of opening and reforming movement in 1978, China made a dramatic transmission from a planned economy to a market economy, sequentially, China started to construct its own capital markets. The Shanghai Stock Exchange (SSE) was established in December 19th, 1990, with eight stocks listed; the Shenzhen Stock Exchange (SZSE) was founded in July 3rd, 1991, with only five companies listed. However, in the past seventeen years, the size of this two exchanges expanded rapidly, 1434 firms are listed in these two exchanges at the end of 2006. The markets segment into different divisions: A- share market, which includes ordinary common shares issued to individual nationals, denominated in RMB. It dominates the equity market of the PRC in terms of both size and activity. B- share market is similar as A- share market. It is also denominated in RMB, but traded in either US dollars (in SSE) or Hong Kong dollars (in SZSE). The main purpose of operating stock markets for Chinese government used to be collecting funds to solve the problems that caused by the state-owned enterprises (SOEs), however, nowadays, the government has realised the importance of the markets and intends to find a way to balance this capitalist ideology into the its socialistic economy.